DaVinci Resolve 12 Essential Training. - Inhofer, Patrick (linkedin.com, 2016)
Learn how to enhance the color, contrast, mood, and style of your video projects with DaVinci Resolve 12, the powerful color grading and color correction software from BlackMagic.